Implementasi Metode Talaqqi dan Musyafahah dalam Meningkatkan Kemampuan Membaca Al-Qur’an Siswa di SD Swasta Salsa - Suriansyah, Muhammad Arsyad (Fitrah: Journal of Islamic Education, 2020)
This study aims to analyze the implementation of talaqqi and musyafahah methods in improving students' reading ability of the Al-Qur'an at Salsa Percut Sei Tuan Private Elementary School. The method used was Classroom Action Research with two cycle’s stages. Each cycle is carried out following the planning, implementation, observation and reflection procedures. Data were collected using observation, interview, test and documentation techniques. The results showed that the students' ability to read Al-Qur'an in pre-action still did not meet the minimum completeness criteria. In cycle 1 the students' ability to read the Al-Qur’an who was able to fulfill the minimum completeness criteria were only 2 students (makharijul huruf), 1 student (sifatul huruf), and 2 students (ahkamul huruf), after learning in cycle 2 increased, so that those who were able to fulfill the minimum completeness criteria into 8 students (makharijul huruf), 8 students (sifatul huruf), and 8 (ahkamul huruf) students. These results indicate that the learning outcomes score has exceeded the specified minimum completeness criteria. The application of this learning method has also received a good response by students; this can be seen from the enthusiasm and increasing attractiveness of students to learn tajwid.